Polymorphisms in micro RNA Genes and Humoral Immune Response to Hepatitis B Vaccine in Iraqi Children and Adolescents - Qasim Sharhan Al-Mayah (Journal of Global Pharma Technology, 2018)
The remarkable reduction in the incidence of hepatitis B virus (HBV) is mainly attributed to the vaccination regime. However, some individual variations in immune response to this vaccine do exist which may be actually referred to as genetic factors. This study aimed to evaluate the role of three single nucleotide polymorphisms (SNP) in microRNA genes, that is, miR-146a G>C, miR-149 C>T and miR-196a2 C>T in the humoral response to HBV vaccine. A total of 86 children and adolescents who had completed the vaccination program from Al-Zahraa Health Center during the period between October 2016 to January 2017 were recruited for this study. Serum levels of anti-HBs IgG was measured with enzyme linked immunosorbent assay (ELISA), DNA was extracted from blood sample and specific primers were used for the amplification of gene fragments corresponding to the SNPs. According to the instructions of the ELISA kit, among the investigated 86 subjects, only 58 (67.44%) had good immune response. Direct sequencing was used for genotyping. In recessive model, the frequency of GC+CC genotypes of miR-146a G>C was significantly higher in responders than non-responders (OR = 2.598, 95% CI = 1.008-6.698, P = 0.046), and the minor allele (C allele) was more frequent among responders than non-responders (OR = 2.16, 95%CI = 1.029-4.532, P = 0.039). The wild homozygous genotype (CC) and miR-196a2 C>T was more frequent in responders than non-responders (OR = 2.881, 95% CI = 1.044-7.953, P = 0.041) with significant effect of dominance model in responders against non-responders (OR = 3.143, 95% CI = 1.210-8.161, P = 0.016). Furthermore, the major allele (allele C) was more frequent in responders than non-responders (OR = 2.724, 95% CI = 1.253-5.922, P = 0.013). These data indicate the important role of miR-146a G>C and miR-196a2 C>T in immune response against HBV vaccine.Key words: Mi RNA, Hepatitis B vaccine, Single nucleotide polymorphisms.